PEMANFAATAN SUMBER DAYA ALAM DESA BAYU SONGGON MELALUI PERAN KKN TEMATIK POSDAYA BERBASIS MASJID - Imam Mashuri (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2018)
The use of good natural resources can improve people's lives. Thematic KKN based on Posdaya in Baitul Ulum mosque, Bayu Village, Songgon Subdistrict, utilizes natural water resources and agricultural land for koi fish breeding with the rice mina system. Besides harvesting rice, it also harvests koi fish. This system can develop natural resources without having to damage the ecosystem. It can even be a source of income for people other than rice.